2018
DOI: 10.12688/f1000research.15985.1
|View full text |Cite
|
Sign up to set email alerts
|

Healing capacity of bone marrow mesenchymal stem cells versus platelet-rich fibrin in tibial bone defects of albino rats: an in vivo study

Abstract: Background: Various techniques for tissue engineering have been introduced to aid the regeneration of defective or lost bone tissue. The aim of this study was to compare the in vivo bone-forming potential of bone marrow mesenchymal stem cells (BM-MSCs) and platelet-rich fibrin (PRF) on induced bone defects in rats’ tibiae. Methods: In total, one defect of 3-mm diameter was created in each tibia of 36 Wistar male rats. There were two groups: group A, left tibia bone defects that received PRF; and group B, right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…21 An additional empty tube was implanted as a control in an attempt to control variables, avoid selection bias, and neutralize any confounders that might affect the results. 16 In this study, stromal inflammatory response (mononuclear cells), vascular changes, fibrous tissue formation, and the presence of MNGCs in the subcutaneous tissues of the rats were evaluated. In all subgroups, the results showed a moderate to severe stromal inflammatory response presented as the recruitment of inflammatory cells, numerous blood vessels and irregular collagen fibers with the presence of MNGCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 An additional empty tube was implanted as a control in an attempt to control variables, avoid selection bias, and neutralize any confounders that might affect the results. 16 In this study, stromal inflammatory response (mononuclear cells), vascular changes, fibrous tissue formation, and the presence of MNGCs in the subcutaneous tissues of the rats were evaluated. In all subgroups, the results showed a moderate to severe stromal inflammatory response presented as the recruitment of inflammatory cells, numerous blood vessels and irregular collagen fibers with the presence of MNGCs.…”
Section: Discussionmentioning
confidence: 99%
“…On days 7 and 30 after implantation, the animals were euthanized by intracardiac overdose of sodium thiopental (80 mg/kg b.w.). 16…”
Section: Animal Study Designmentioning
confidence: 99%
“…The sample size was calculated based on the data of reference Rady et al, 22 that the maximum difference between the three groups mean is 1.08 and the estimated pooled standard deviation is 0.96. Assuming the alpha error 0.05 and power 0.8 a number of 17 cases per group is required adding 3 cases for anticipated missing data it results in 20 cases per group a total of 60 cases.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…25,26 Fibrin gels encapsulating chondrocytes, bone marrow-derived mesenchymal stem cells (BMSCs), fibroblasts, and osteoblasts have demonstrated that these biomaterials promote cellular adhesion and support proliferation, growth, and respective tissue differentiation. [27][28][29][30][31][32][33] Our own work utilized fibrin in combination with hyaluronic acid as a hybrid gel matrix for cartilage and bone TE. 34,35 In TE, many cell sources are considered to provide progenitor or mesenchymal stem cells required for regeneration.…”
Section: Introductionmentioning
confidence: 99%